Response of Medical Professional Towards Subsequent Communication, Patient Emotion and Visit Length - Sabahat Ali Zaidi, Shamaila Zamir, Muhammad Faisal Javaid, Sundas Ali, Maheen Zehra, Gul Muhammad Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was designed to explore the association between the responses of clinician towards the emotional expression of patients which effect the length of patient’s visit in public hospital as the flow of patients is more in public hospitals and clinicians have to manage according to the time as well. Method: This exploratory research was conducted in a public sector tertiary care hospital in Lahore. Data was collected in the form of audio recordings which are transcribed and coded in terms of emotional expression of patients and empathetic response of clinicians. Data was analyzed using SPSS version 25. Descriptive statistics was used to report gender and age of patients as well as clinicians. Pearson correlation was used to explore the association between emotional expression of patients and empathetic response of clinician. Association of subsequent emotional expression of patients was also explored in terms of length of visit and clinicians’ response. Results: The results revealed that the timing of emotional expression of patients (single time) has a positive relationship with the empathetic response of clinicians (r= 0.67, P=.001) and the timing of subsequent emotional expression of patients has a negative relationship with the empathetic response of clinicians (r= -0.93, P=.000). Conclusion: The clinician respond empathetically on emotional expression of patient can help in reducing the subsequent expression of emotions among patients, ultimately visit length will be reduced.